Patterns of Sensitivity to Parenting and Peer Environments: Early Temperament and Adolescent Externalizing Behavior - Tung, Irene (J Res Adolesc, 2018)
Although parenting behavior and friendship quality predict adolescent externalizing behaviors, individual differences in temperament may differentially affect susceptibility to these factors over time. In a multi-method and multi-informant study of 141 children followed prospectively from toddlerhood to adolescence, we tested the independent and interactive associations of age 3 reactive temperament (e.g., negative emotionality) and age 13 observed parenting (i.e., positive and negative behavior) and friendship (i.e., conflict and warmth), with multi-informant ratings of age 15 aggression and rule-breaking behavior. Negative parenting predicted growth in parent-rated externalizing behavior, but only for adolescents with early reactive temperament. Temperament did not affect sensitivity to positive parenting or friendship. Results are discussed in the context of differential susceptibility theory and intervention implications for adolescents.